2018
DOI: 10.2106/jbjs.oa.18.00005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Rotator Cuff Tear Is Influenced by Demographics and Characteristics of the Area Where Patients Live

Abstract: Background:Atraumatic rotator cuff tear is a common orthopaedic complaint for people >60 years of age. Lack of evidence or consensus on appropriate treatment for this type of injury creates the potential for substantial discretion in treatment decisions. To our knowledge, no study has assessed the implications of this discretion on treatment patterns across the United States.Methods:All Medicare beneficiaries in the United States with a new magnetic resonance imaging (MRI)-confirmed atraumatic rotator cuff tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 54 publications
(44 reference statements)
1
24
0
Order By: Relevance
“…Out of the 50 million people impacted by chronic pain, only 12 million people in the United States accessed outpatient physical or occupational therapy [13]. Across common MSK conditions, like low back pain and rotator cuff tear, physical therapy utilization ranges from 3-10% with significant variation across health referral regions [14][15][16]. Utilization is limited for physical therapy services in part by the available workforce.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 50 million people impacted by chronic pain, only 12 million people in the United States accessed outpatient physical or occupational therapy [13]. Across common MSK conditions, like low back pain and rotator cuff tear, physical therapy utilization ranges from 3-10% with significant variation across health referral regions [14][15][16]. Utilization is limited for physical therapy services in part by the available workforce.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that there are significant differences in surgical indications between surgeons 9 as well as geographic variances in the incidence of rotator cuff surgery. 4,25 We sought to better define patient-and tear-related factors that may play a role in surgical decision making. In our cohort, the surgical team offered a balanced discussion regarding options for the treatment of the newly painful cuff tear and patients were counseled toward conservative treatment and continued surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Medicare claims in the year prior to the index PHF were used to estimate the Charlson Comorbidity Index (CCI), 121,122 the Frailty Risk Index (FRI) score, 123 and quintiles of patient-specific total Medicare spending in the year prior to index. 96,[124][125][126] Prior healthcare spending has been shown to be indicative of patient health status and health care utilization preferences. 96,125,126 For the IV-CFA, the five age groups, CCI, FRI, and the prior health cost quintiles were each specified as index variables so that concept "cut-offs" produced by IV-CFA implied monotonic relationships (e.g.…”
Section: Reference Class Factorsmentioning
confidence: 99%
“…96,[124][125][126] Prior healthcare spending has been shown to be indicative of patient health status and health care utilization preferences. 96,125,126 For the IV-CFA, the five age groups, CCI, FRI, and the prior health cost quintiles were each specified as index variables so that concept "cut-offs" produced by IV-CFA implied monotonic relationships (e.g. a cut-off of less than or equal to age group 3 implies all patients age less than or equal to 79, versus 80 and above).…”
Section: Reference Class Factorsmentioning
confidence: 99%